TRENDS IN UNIVERSITY AUTONOMY IN THE EU IN THE PRE-PANDEMIC DECADE - Mospan, Natalia (The Modern Higher Education Review, 2024)
The pre-pandemic decade (2010–2019) is likely to have become an era of rapid spread and development of university autonomy in the EU. Therefore, the article makes an effort to reveal the trends in developing university autonomy in the pre-pandemic decade, which could contribute to understanding this phenomenon in the post-pandemic times. The systematic examination of 24 scientific resources published primarily on the Web of Science Core Collection database in 2010–2019 makes it possible to reveal the following trends in university autonomy development on organizational, financial, academic and staff levels. The research covers the time frame from 2010 to 2019 – the official beginning of the COVID-19 pandemic. The research insights show that in the pre-pandemic decade, university autonomy is characterised by diverse implementation and uneven distribution in the EU, as well as different access to financing. This diversity and unevenness may have affected the universities’ decision-making during the COVID-19 pandemic. The research results can contribute to the understanding of the phenomenon of university autonomy. This research is made within the framework of the implementation of the European Union project Erasmus + “University autonomy in the development of democratic values ​​in higher education: experience of EU countries for Ukraine.”